Analysis of Sharia Hotel Tourism Performance Factors in the Seribu Islands, DKI Jakarta in 2024 - Lukman Lukman; Hepi Prayudiawan; Suhendra Suhendra; Bahrul Yaman; Awani Ceria Luksita (Cahaya Abadi Publisher, 2025)
Sharia tourism has become one of Indonesia’s leading sectors contributing significantly to national foreign exchange earnings. In line with this development, the hospitality industry plays a strategic role in realizing competitive and sustainable sharia-based tourism. This study aims to analyze the determinants that influence the performance of sharia hotel tourism in Indonesia. A quantitative research approach was employed, utilizing Partial Least Squares (PLS) as the main analytical tool to test the proposed model and hypotheses. The findings indicate that the performance of sharia hotel tourism can be assessed through several key indicators, including employment absorption, improvement of community economic welfare, as well as environmental and socio-cultural sustainability. Furthermore, empirical evidence reveals that the performance of sharia hotel tourism is significantly affected by various factors such as environmental conditions, quality of services, governance systems, accessibility, infrastructure, facilities, and regulatory frameworks. Among these, regulatory factors demonstrate strong linkages with aspects of location, capital, and promotional efforts, which collectively determine the competitiveness and attractiveness of sharia-compliant hotels. The study emphasizes the importance of comprehensive governance and policy support in strengthening sharia tourism performance. Hence, effective collaboration among stakeholders, including government, hotel managers, and local communities, is crucial to enhance Indonesia’s position as a global center for sharia tourism.